Linking Representation and Reasoning: An Analysis of Mathematical Communication in Algebraic Word-Problem Solving - Najmy, Zhafirah; Nurrahmawati, Nurrahmawati; Arcat, Arcat; Afri, Lusi Eka (EDUPEDIA Publisher, 2026)
Purpose – Mathematical communication is essential in 21st-century mathematics learning because it enables students to represent, explain, and interpret ideas when solving contextual problems. This study aimed to describe seventh-grade students’ mathematical communication in solving algebraic word problems. Methodology – A qualitative descriptive design was used. Seventh-grade students at SMP Negeri 3 Rambah Hilir were purposively selected to represent high-, middle-, and low-achieving groups based on classroom performance and test results. Data were collected using an algebraic word-problem written test and semi-structured interviews. Analysis followed data reduction, data display, and conclusion drawing. Mathematical communication was examined using three indicators: (1) translating contexts/diagrams into mathematical language or models; (2) explaining mathematical ideas and relationships in writing; and (3) reading and interpreting written mathematical representations. Findings – Students’ mathematical communication was low. High-achieving students met all indicators, producing accurate representations and coherent written reasoning. Middle-achieving students generally met indicators (1) and (3), but their written explanations (indicator 2) were incomplete or unclear. Low-achieving students struggled across indicators, particularly in forming algebraic models and interpreting representations, leading to incorrect or incomplete solutions. The results highlight the need for explicit scaffolding of representation, written explanation, and interpretation in algebraic word-problem instruction. Novelty – This study offers an indicator-based profile of mathematical communication in algebraic word-problem solving across achievement levels using combined test and interview evidence. Significance – The findings support teachers and curriculum developers in designing learning activities and assessments that strengthen communication, representation, and reasoning in junior secondary algebra.